AKTUALISASI LONG LIFE EDUCATION PRESPEKTIF HADIS RIWAYAT IBNU MAJAH NOMOR 220 - Febrian, M Agil; Lubis, Zulfahmi; Sirait, Azyana Alda; Jarkasih Hrp, Ibnu Alwi; Qomariah, Siti (Reflektika, 2023)
This article is entitled Actualization of Long Life Education Perspective Hadith History of Ibnu Majag Number 220. This research aims to find out the Takhrij of H.R. Ibnu Majah No. 220, to find out the actualization of life long education perspective of H.R Ibnu Majah no. 220. This research uses library research, namely research conducted by using literature (libraries) in the form of books, notes or reports of research results from previous research. After the data was analyzed, the research results were obtained, that Long Life Education is a concept of continuous and continuous learning (continuing-learning) from the cradle to the end of life. From the Prophet's point of view, there are two components in lifelong education life. Prenatal education is education that occurs before birth and covers topics such as choosing a partner, marriage, and pregnancy. The second type of education is postnatal, or education that takes place after birth and includes education after the birth period, including: infant, childhood, childhood and adult education. This statement is in accordance with HR. with obligations as a servant of Allah SWT. Muslims here include both men and women.Â Â